Diretrizes curriculares nacionais das profissões da saúde : um estudo transversal 2001-2004 - Costa, Dayane Aparecida Silva (2016)
In order to induce changes in the graduation in Healthcare and to improve the Unified Healthcare System – SUS, the Education Ministry – MEC instituted National Curricular Guidelines – DCN for the fourteen Healthcare related professions. This movement of construction of the DCN is the result of a defense process to educate citizens with a critical view and who agree with the principles and guidelines which SUS preconizes. Therefore, the present study has the goal of analyzing the DCN of the fourteen Healthcare related professions proposed between the period of 2001 and 2004. An exploratory descriptive study has been realized, according to the documental analysis of the DCN, regulated by the Resolution nº287/1998. The data acquiring was realized through the MEC/Portal Site consult, in which were found the resolutions for the fourteen Healthcare related courses. For the proper analysis of the data, an analytic matrix has been used. The matrix contained two axis: Curriculum and Professional Profile, containing the following categories: student evaluation process; teaching-learning process; curricular organization; Professional profile; healthcare; healthcare education and healthcare management. The results reveal gaps related to the articulation of the graduation with the real demands of SUS; there was few focus in innovative concepts, with healthcare perspectives of amplified care; a Professional profile with potent characteristics for SUS establishment; the teaching-learning process shows a initial advance referring to the construction of knowledge centered in the student; the student evaluation that points to a traditional approach. Also, contradictions were verified between conservative and innovative curricular principles; some DCN highlighted technicalist approaches and permissed ambiguous comprehension, showing the lack of clarity to explain the analyzed categories. Considering the DCN as a document that grounds the political pedagogic projects, by ethics, social responsability and commitment. It is expected the ampliation, better explaining and changing in the conservative procedures to seek the promotion, prevention and recuperation and/or rehabilitation, according to SUS statements, throught which the obstacle of integrating teaching, service and social demands will be overcome. Therefore this study proposes the catenation of reflections and possible reviews of the DCN, in the parameters of the Medicine course’s DCN, reviewed in 2014, which brought innovative and significant guiding for a formation directed to the demands of SUS and the needs of the population.